Fractal analysis approach in the characterisation of cerebrovascular complexity in asymptomatic cerebral small vessel disease - Aminuddin, Niferiti (2023)
Cerebral small vessel disease (CSVD) refers to a spectrum of clinical and neuroimaging findings caused by pathological damage of small vessels of the cerebral parenchyma. Cerebral white matter hyperintensity (WMH) is one of the commonest neuroimaging findings of CSVD. Often, CSVD is diagnosed once the symptoms developed. Detection of the underlying vascular structural changes might facilitate early disease risk stratification and disease monitoring as vascular alteration precedes cerebral parenchymal injury. Of interest, fractal analysis allows us to quantitatively measure the complexity of the cerebral vascular structure in terms of fractal dimension (Df). The cerebral vascular Df changes are indicative of inefficient tissues perfusion which renders the cerebral parenchyma vulnerable to damage. The aim of this study is to explore a novel vascular neuroimaging marker of asymptomatic CSVD by characterising the complexity of the circle of Willis (CoW) and its tributaries as measured by Df. An exploratory cross-sectional study was conducted involving 22 subjects of age between 25 - 75 years old with low to moderate QRISK2 score who underwent magnetic resonance imaging/angiography (MRI/MRA) examination. These subjects presented with or without WMH. The cerebral vascular complexity of the MRA image was characterised using Df. The cerebral vascular Df was compared between asymptomatic subjects with (WMH+; n = 8) and without cerebral WMH (WMH-; n = 14). Furthermore, cerebral vascular Df was also compared between asymptomatic subjects with both CSVD risk factors and cerebral WMH (RF+ & WMH+; n = 6), subjects with CSVD risk factors only (RF+ & WMH-; n = 5), and subjects without both CSVD risk factors and cerebral WMH (RF- & WMH-; n = 9). Simple linear regression (SLR) was performed between QRISK2 score and cerebral vascular Df. Mean cerebral vascular Df was significantly lower in the WMH+ group than WMH- group. Moreover, the mean cerebral vascular Df of the RF+ & WMH- and RF+ & WMH+ groups were significantly lower than RF- & WMH- group. The SLR model had indicated that increased QRISK2 score significantly predicted reduction in cerebral vascular Df. The cerebral vascular Df was reduced in the subjects with CSVD risk factors and asymptomatic CSVD subjects with WMH. The SLR model had indicated that QRISK2 score significantly predicted cerebral vascular Df. The results indicate that cerebral vascular Df is a promising biomarker of asymptomatic CSVD subjects with WMH. Larger-scaled studies are required to explore its potential in a broader population setting.